Analisis Strategi Komunikasi Pemasaran Tim Skin Game Dalam Meningkatkan Brand Awareness Melalui Media Sosial Tik-Tok - Simanjuntak, Agnes Immanuela Mayora; Shabrina, Almira (Professional: Jurnal Komunikasi dan Administrasi Publik, 2024)
Skin Game is a local skincare brand that sells various facial skincare products. The utilization of Tik-Tok social media as a means of conducting marketing communication strategies has been carried out by the Skin Game team. Tik-Tok is one of the social media that has become a platform for many brand entrepreneurs to market their products. Through Tik-Tok social media, many companies make this social media a means to promote the products or services they sell, this greatly influences the purchasing decisions of consumers which will increase sales of products or services from the company. The researcher's objective in conducting this research is to find out how the Skin Game team's marketing communication strategy increases brand awareness through Tik-Tok social media. This research uses qualitative research methods, using a case study approach and is supported by the constructivism paradigm. The data collection technique was conducted through semi-structured interviews, participatory observation, and documentation. Researchers used marketing communication strategies, namely message strategies and media strategies. Researchers found that there are several message strategies and media strategies used by the Skin Game Team in the marketing communication strategy through Tiktok social media.